ANALYSIS OF HEAVY EQUIPMENT PRODUCTIVITY IN THE PHASE II KASABLANKA KUNINGAN APARTMENT DEVELOPMENT PROJECT - GALI PRIBADI; BILHAN GAMALIEL HARTANTO (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2023)
In building construction projects, especially in the excavation stage, the use of heavy vehicles is essential and plays an important role in determining the success of apartment building construction. The production capacity of these heavy vehicles is critical to the progress of the project. The importance of production capacity analysis makes this calculation crucial. This study aims to measure the production capacity of heavy vehicles in the second phase of the Kasablanka Kuningan apartment building construction project, including asphalt finishers, dump trucks, pneumatic tire rollers, and tandem rollers. Using the volumetric method, this study calculates the volume and production capacity of heavy equipment, with results showing that productivity is in accordance with the predetermined schedule.